The Role of Social Business in Environmental Protection through Poverty Alleviation - Alam, Md. Wahidul; Shakil, Mohammad Hassan; Azam, Md. Kazi Golam; Tasnia, Mashiyat (Global Disclosure of Economics and Business, 2014)
Social Business runs for the welfare of people rather to profit maximization. In the economic system of Bangladesh there are mainly two types of organization models. Companies of private sector sell products or services to make profit while non-profit organizations are financed by the government. When both the governments and private sector reach their limits, charity organizations fill up the deficiency. Nowadays, we have forgotten to involve the poor into the economy. And exactly that target group is full of potential but has never had a real opportunity. Only such opportunities can be provided to them through social business. The study is of analytical and theoretical in nature and based on secondary data. It encompasses the fact that success of social business sector in Bangladesh is noteworthy as Bangladesh is taking various successful steps to go ahead in poverty alleviation and environmental protection through new alternative arrangement named Social Business. The paper depicts that Social Businesses of Bangladesh is trying to contribute in environmental protection through poverty alleviation by its different extensive programs. Various new integrated model and new Social Business idea will support in this regard. The Social Business can easily overcome the impediments in environmental protection and poverty alleviation by implementing policy formulated in this study.